Diabetes group education on self-management for people with type 2 diabetes mellitus, changes in nutritional knowledge, diet and clinical outcomes at 12 weeks - Thelma Grímsdóttir 1990- (2017)
Background: Type 2 diabetes mellitus (T2DM) is a severe and progressive condition. Its prevalence is increasing globally, with the estimated prevalence of 8.8% in the age group of 20-79 years old in 2015. Self-management programmes for people with T2DM to educate people in a structured way have in the recent years become an important factor in T2DM treatment. For people with T2DM reducing HbA1c levels decreases the risk of cardiovascular disease, microvascular complications of diabetes and death. One of the key factors in self-management programmes is to improve nutrition knowledge as it is one of the factors that support good dietary choices. The aim of this study is to evaluate the effects of a self-management group programme for people with type 2 diabetes mellitus on nutrition knowledge, diet and clinical outcomes at 12 week follow-up. Methods: Intervention study where the participants had a follow-up after 12 weeks. Participants were 24, 13 men and 11 women, outpatients at the Department G3 at the Landspitali University Hospital (LSH) in Iceland and were all diagnosed with type 2 diabetes mellitus. The mean age of participants was 56 ±11 years. At baseline participants answered questionnaires, 24-hour dietary recall, had anthropometry measurements, went for a blood- and urinary tests and went through the four-hour self-management programme. At week-12, participants answered the same questionnaires as at baseline, had anthropometry measurements and went for a blood test and delivered a urine sample. Nutrition knowledge, dietary intake and clinical outcomes at baseline were compared with the outcomes after 12 weeks. Results: No significant difference was found in participant’s meal frequency or diet between baseline and week-12. There was no significant difference in nutrition knowledge between baseline and week-12. The Diabetes Knowledge Scale (DKS) scores were indicative higher after 12 weeks compared to baseline (p<0.1). No difference was found in weight, BMI, waist circumference and blood pressure ...